Late hepatic toxicity surveillance for survivors of childhood, adolescent and young adult cancer: Recommendations from the international late effects of childhood cancer guideline harmonization group. (November 2021) - Bardi, Edit; Mulder, Renée L.; van Dalen, Elvira C.; Bhatt, Neel S.; Ruble, Kathy A.; Burgis, Jennifer; Castellino, Sharon M.; Constine, Louis S.; den Hoed, Caroline M.; Green, Daniel M.; Koot, Bart G.P.; Levitt, Gill; et al.
Highlights: Cancer survivors are at risk for chronic liver disease, especially those treated with radiotherapy to the liver. This guideline provides recommendations for the surveillance of late hepatotoxicity. Physical examination and measurement of serum liver enzyme concentrations once at entry into long-term follow-up is recommended for at-risk survivors. Abstract: Background: Survivors of childhood, adolescent and young adult (CAYA) cancer may develop treatment-induced chronic liver disease. Surveillance guidelines can improve survivors' health outcomes. However, current recommendations vary, leading to uncertainty about optimal screening. The International Late Effects of Childhood Cancer Guideline Harmonization Group has developed recommendations for the surveillance of late hepatotoxicity after CAYA cancer. Methods: Evidence-based methods based on the GRADE framework were used in guideline development. A multidisciplinary guideline panel performed systematic literature reviews, developed evidence summaries, appraised the evidence, and formulated recommendations on the basis of evidence, clinical judgement, and consideration of benefits versus the harms of the surveillance while allowing for flexibility in implementation across different health care systems. Results: The guideline strongly recommends a physical examination and measurement of serum liver enzyme concentrations (ALT, AST, gGT, ALP) once at entry into long-term follow-up for survivors treated with radiotherapy potentially exposing the liver (moderate- to high-quality evidence). For survivors treated with busulfan, thioguanine, mercaptopurine, methotrexate, dactinomycin, hematopoietic stem cell transplantation (HSCT), or hepatic surgery, or with a history of chronic viral hepatitis or sinusoidal obstruction syndrome, similar surveillance for late hepatotoxicity once at entry into LTFU is reasonable (low-quality evidence/expert opinion, moderate recommendation). For survivors who have undergone HSCT and/or received multiple red blood cell transfusions, surveillance for iron overload with serum ferritin is strongly recommended once at long-term follow-up entry. Conclusions: These evidence-based, internationally-harmonized recommendations for the surveillance of late hepatic toxicity in cancer survivors can inform clinical care and guide future research of health outcomes for CAYA cancer survivors.